Parent‐implemented brief functional analysis in the home. (20th August 2020) - Gerow, Stephanie; Rivera, Gabby; Radhakrishnan, Supriya; Davis, Tonya N.
Abstract: The purpose of this study was to evaluate the accuracy, feasibility, and social validity of a parent‐implemented brief functional analysis in the home. Three toddlers with developmental delay and their mothers participated in the study. The brief functional analysis required 2.4–3.5 hr to complete and parents rated the assessment positively on a social validity questionnaire. Following the brief functional analysis, treatment evaluations were conducted using single‐case research designs. Results suggest that parent‐implemented brief functional analysis in homes can lead to the development of an effective intervention. These results, along with previous research, indicate practitioners working in homes should consider brief functional analysis, when appropriate.